2005
DOI: 10.1182/blood-2004-06-2480
|View full text |Cite
|
Sign up to set email alerts
|

Blood and bone: two tissues whose fates are intertwined to create the hematopoietic stem-cell niche

Abstract: The mechanisms of bone and blood formation have traditionally been viewed as distinct, unrelated processes, but compelling evidence suggests that they are intertwined. Based on observations that hematopoietic precursors reside close to endosteal surfaces, it was hypothesized that osteoblasts play a central role in hematopoiesis, and it has been shown that osteoblasts produce many factors essential for the survival, renewal, and maturation of hematopoietic stem cells (HSCs). Preceding these observations are stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
370
0
10

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 542 publications
(390 citation statements)
references
References 87 publications
7
370
0
10
Order By: Relevance
“…Disruption of the SDF-1/CXCR4 axis has been reported to lead to stem cell mobilization in several animal models (see [18][19][20][21] ). The comparison of data obtained using an animal model and by studying patients with PMF provides evidence that alterations in CXCR4 expression or SDF-1 levels may be, at least partially, responsible for the abnormal stem/progenitor cell trafficking observed in PMF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of the SDF-1/CXCR4 axis has been reported to lead to stem cell mobilization in several animal models (see [18][19][20][21] ). The comparison of data obtained using an animal model and by studying patients with PMF provides evidence that alterations in CXCR4 expression or SDF-1 levels may be, at least partially, responsible for the abnormal stem/progenitor cell trafficking observed in PMF.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the liver, SDF-1 is produced in the marrow by several cell types, including osteoblasts 17 . Recent genetic studies have demonstrated that osteoblasts are critical cellular elements for stem cell maintenance and development [18][19][20] . Stem cells are believed to reside in close proximity to the endosteal surface of the bone, where osteoblasts are also located 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…OPG is secreted by osteoblasts within the stem cell niche [33] and inhibits the differentiation of osteoclasts [34]. Induction of cell proliferation does not belong to its known qualities.…”
Section: Il-32 Attenuates Bm Cytotoxicities In a Murine Chemotherapy mentioning
confidence: 99%
“…VLA-4 integrin deregulation is consistently found in solid tumors and in AML and has shown to be responsible for tumor drug resistance [114][115][116][117]. VLA-4 and its ligand fibronectin are also important for HSC localization and retention to osteoblasts and the endosteal niche [118,119].…”
Section: Chemotaxis Towards Bonementioning
confidence: 99%